Lung Cancer: Targeted Therapy in 2025 - Nicole Bouchard; Nathalie Daaboul (Current Oncology)
Lung cancer treatment has changed in the last twenty years since the discovery of EGFR mutations. In this article, we will review the current state of the art for non-small cell lung cancer (NSCLC) actionable genomic alterations (AGA). AGAs are mostly found in lung adenocarcinomas, a subtype of non-small cell lung cancers. We will focus on the current treatment for EGFR mutations, ALK fusions, ROS1 fusions, BRAF V600E mutations, MET exon 14-skipping mutations, RET fusions, KRAS G12C mutations, ERBB2 mutations (also called HER2 mutations), and NTRK fusions. We will also touch on the key toxicities associated with these medications. Treatments are mostly available for the metastatic stage, but we will also discuss adjuvant therapy for EGFR mutations and ALK fusions, as well as stage III post-chemoradiotherapy treatment for EGFR lung cancer.